Proceedings of the 18th Conference of the Simone de Beauvoir Society : yesterday, today and tomorrow - Duranti, Andrea; Tuveri, Matteo (Cambridge Scholars Publishing, 2017)
On April 14, 1986, Simone de Beauvoir died in Paris. She was the "prettiest Existentialist", who during her long and intense life had observed, described, analytically deconstructed and effectively changed the world that surrounded her, "one word at a time". An engaged intellectual like her life partner and comrade Jean-Paul Sartre, she took actively part in most of the main social and political struggles of the 20th century, including, first and foremost, women's emancipation and self-determination, as well as the decolonisation of French Algeria, and the denouncement of American imperialism